Union citizenship as an instrument for the protection of rights and means of fostering cohesion among European citizens - Tching, Maria Rosa Oliveira (2014)
In a European Union still ridden with social and economic imbalances, the author calls for greater convergence between citizenship and fundamental rights in order to make the European citizen a more complete being, enjoying rights resulting from the European citizenship status, including the rights enshrined in Article 20 of the Treaty on the Functioning of the European Union (non-discrimination, freedom of movement, residence, political and civic participation, diplomatic protection) and the rights listed in the Charter of Fundamental Rights of the European Union and the European Convention on Human Rights and Fundamental Freedoms. The author emphasizes the importance of the European citizenship status as an instrument of protection of rights and an element of cohesion among Union citizens – and, in this context, highlights the case law of the honoree Judge Cunha Rodrigues as a precursor to a new dimension of Union citizenship and the consequent widening of the scope of European Union law.